DOI: 10.22215/etd/2021-14678
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Urban Settings on Airflow Characteristics for Urban Air Mobility Applications

Abstract: The urban wind environment is characterized by complex flow structures and high levels of turbulence due to the densely built up regions and the presence of tall buildings. This renders the flight operations in urban areas challenging since the turbulent airflow characteristics may impair the control system of the flying vehicles, leading to loss of control, which could be catastrophic considering that the areas are densely populated. This thesis investigates the urban airflow characteristics that are expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This is exemplified by data point 30 for the west-south-west wind direction and points 29, 32, and 35 for the south wind direction. This could indicate the presence of red zones [51] when it comes to safe operations of UAT. More locations in the urban environment should be investigated in future research to identify potential red zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by data point 30 for the west-south-west wind direction and points 29, 32, and 35 for the south wind direction. This could indicate the presence of red zones [51] when it comes to safe operations of UAT. More locations in the urban environment should be investigated in future research to identify potential red zones.…”
Section: Discussionmentioning
confidence: 99%
“…The ADRC flight controller was able to further reduce the lateral accelerations to below the minimum discomfort levels. With the data points that were used to create the urban airflow disturbances, it was observed that certain locations in the urban airspace may experience higher turbulence regardless of incoming wind direction, thereby indicating the presence of red zones [51]. The red zones could be different for various types of operations, such as organ delivery, light cargo, or passenger transportation.…”
Section: Discussionmentioning
confidence: 99%
“…Within the research group where the work presented in this thesis was conducted, a colleague completing a Masters thesis conducted an experimental investigation into Urban Airflow considering UAM [5]. This involved performing wind tunnel tests with a scale model of a urban centre, Toronto was used.…”
Section: Experimental and Computational Urban Air-flow Researchmentioning
confidence: 99%
“…The empirical airflow data were collected for a scaled urban setting extracted from downtown Toronto. The scale model was subjected to various wind directions with wind velocity and turbulence profiles that are similar to the ones encountered in an urban environment [5]. The data are presented as a Power-Spectral Density (PSD) plot in the u, v, and w directions for a specific location in the city.…”
Section: Urban Air Flow Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation